MODULASI RESPONS KECEMASAN DAN FUNGSI MOTORIK OLEH EKSTRAK Solanum torvum Sw.: STUDI IN VIVO BERBASIS ELEVATED PLUS MAZE, OPEN FIELD TEST, DAN UJI KOORDINASI MOTORIK - Fanny Rahmadhani. N; Wahyuni Wahyuni; Hariana Hariana; Maulidyah Maulidyah; Nur Illiyyin Akib; Suryani Suryani; Lidya Agriningsih Haruna; La Ode Muhammad Julian Purnama; Adryan Fristiohady (Fakultas Farmasi UMI, 2026)
Anxiety disorder is one of the most common psychiatric conditions globally with a continuously increasing prevalence, necessitating the exploration of natural products as safer therapeutic alternatives. This study aimed to evaluate the anxiolytic activity of ethanol extract of Solanum torvum Sw. fruit in male BALB/c mice and to assess its effect on motor coordination function. Mice were divided into six groups (n=3 per group): normal control (distilled water), negative control (0.5% Na-CMC), positive control (Amitriptyline 25 mg/kg BW), and extract dose groups of 100, 200, and 400 mg/kg BW. Phytochemical screening was conducted qualitatively, while anxiolytic activity was evaluated using the Elevated Plus Maze (EPM) with %OAE and %TSOA parameters, and the Open Field Test (OFT) with parameters of time spent in the center zone and center zone entries. Motor coordination function was assessed using the rotarod test with parameters of latency to fall and longest duration to stay, and data were analyzed using One-Way ANOVA followed by Post Hoc Tukey test. Phytochemical screening results showed that the extract positively contained alkaloids, flavonoids, tannins, saponins, and terpenoids/steroids. EPM test results showed a significant increase in %OAE and %TSOA parameters in the 400 mg/kg BW dose group compared to the negative control (p < 0.05). In the OFT, the 400 mg/kg BW dose group showed an increase in time spent in the center zone (40.67 ± 4.73 seconds) and center zone entries (11.67 ± 1.53) which were not significantly different from the positive control Amitriptyline (p = 0.954). The rotarod test confirmed that all extract doses did not impair motor coordination, as indicated by no significant differences in latency to fall and longest duration to stay among treatment groups compared to the normal control (p > 0.05). In conclusion, the ethanol extract of Solanum torvum Sw. fruit at a dose of 400 mg/kg BW demonstrated anxiolytic activity equivalent to Amitriptyline without impairing motor coordination function, thus showing potential for development as a safe natural anxiolytic agent; however, further studies with larger sample sizes and biomarker measurements are needed to confirm the underlying molecular mechanisms.